THE EFFECT OF TEAM-GAME-TOURNAMENT TECHNIQUE ON ACADEMIC ACHIEVEMENT AND LONG-TERM RETENTION OF STUDENTS IN TEACHING MATHEMATICS AND STUDENTS’ OPINIONS - Sibel CENGİZHAN (International Journal of Eurasia Social Sciences, 2017)
The objective of the study determine the effect of team-game-tournament technique in teaching Mathematics on students’ academic achievement and long-term retention and to obtain the students’ opinions. The mixed model was used in the study. The sample group of the study consisted of 53 students from two classes studying at 5th grade of a secondary school located in İstanbul. Experimental and control groups were selected by using random sampling method and the class of 31 students were identified as experimental group and the class of 22 people were identified as control group. In the analysis of the qualitative data obtained from the semi-structured interview form, descriptive analysis technique was used. In this study was concluded from the quantitative data obtained that team-game-tournament technique increased the academic achievement and was more successful compared to the traditional education; whereas, it was not effective in providing the long-term retention. When the qualitative data obtained from the study were examined, it was concluded that the team-game-tournament technique developed in-class social relations, the lesson more fun, provided convenience in terms of understanding, increased the participation to the lesson, perspectives to the math lesson changed positively.